Dick Effect in a Microwave Frequency Standard Based on Laser-Cooled 113Cd+ Ions. (14th January 2015) - Zhang, Jian-Wei; Miao, Kai; Wang, Li-Jun
Abstract: The Dick effect is one of the main limits to the frequency stability of a passive frequency standard, especially for the fountain clock and ion clock operated in pulsed mode which require unavoidable dead time during interrogation. Here we measure the phase noise of the interrogation oscillator applied in the microwave frequency standard based on laser-cooled 113 Cd + ions, and analyze the Allan deviation limited by the Dick effect. The results indicate that the Dick effect is one of the key issues for the cadmium ion clock to reach expected frequency stability. This problem can be resolved by interrogating the local oscillator continuously with two ion traps.